Improvement of Natural Grasslands on the Nilgiri Plateau - Gupta, S. C.; Rege, N. D. (Indian Forester, 1965)
The natural grasslands are a great asset to the Nilgiris but these are deteriorated due to misuse and overgrazing leading to excessive soil erosion. The authors have dealt with the basic problems of these grasslands and have emphasised the importance-1. Controlled grazing; 2. Adoption of soil conservation measures; 3. Improvement of grassland vegetation; and 4. Change in the administrative policy, for the amelioration of these grasslands in the Nilgiris.